2022
DOI: 10.3390/microbiolres13040068
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Antibiotic Susceptibility Patterns of Streptococcus agalactiae Strains Isolated from Women in Yaounde, Cameroon

Abstract: Group B Streptococcus (GBS), a commensal in the body, causes a wide range of infectious diseases. This bacterium is dangerous for pregnant women and their babies, in whom it is responsible for early neonatal bacterial sepsis (EOS). The colonisation levels of GBS and its resistance profile to antibiotics provide important information that is useful for orienting prevention strategies. There are few data available on the subject on the determination of resistance phenotypes in Cameroon. We therefore aimed to det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This raises concerns about the use of ampicillin since 1996 in the United States for preventing the vertical transmission of GBS, which could contribute to the development of MDR GBS, especially in Japan [80]. African authors found that at least 55% of GBS isolates from Cameroonian women became MDR [81]. The data presented in the tables are difficult to compare due to some differences in the interpretation guidelines and evolving changes in the various years of the two usage systems, and some authors did not strictly indicate which guidelines they used.…”
Section: Resistance To Mlsb Antibioticsmentioning
confidence: 99%
“…This raises concerns about the use of ampicillin since 1996 in the United States for preventing the vertical transmission of GBS, which could contribute to the development of MDR GBS, especially in Japan [80]. African authors found that at least 55% of GBS isolates from Cameroonian women became MDR [81]. The data presented in the tables are difficult to compare due to some differences in the interpretation guidelines and evolving changes in the various years of the two usage systems, and some authors did not strictly indicate which guidelines they used.…”
Section: Resistance To Mlsb Antibioticsmentioning
confidence: 99%
“…A major concern is the ability of the bacterium to acquire resistance to multiple antibiotics, often leading to treatment failure. Djuikoue and co-authors [ 7 ] report a prospective cross-sectional study in a hospital setting in Cameroon, by collecting and analyzing vaginal and urine swabs collected from 163 women, and the results obtained showed that non-pregnant and pregnant women were, respectively, 37% and 59.7% colonized with S. agalactiae. The authors highlight the importance of monitoring this bacterium antimicrobial resistance in pregnant women and newborns [ 7 ].…”
mentioning
confidence: 99%